The community food environment as an effect modifier of the relationship between racial discrimination and food insecurity among adults in Southern Brazil - Emanuele Bottega de Vargas; Mariane da Silva Dias; Ilaine Schuch; Priscila Bárbara Zanini Rosa; Marcos Fanton; Raquel Canuto (BMC, 2024)
Abstract Background Racial discrimination is linked to unhealthy food environments and a higher prevalence of food insecurity. However, no study has explored their interrelated effects. We analyzed the relationship between racial discrimination, community food environment, and food insecurity in adults of different socioeconomic status. We also investigated the potential modifying effect of the food environment on the relationship between racism and food insecurity. Methods This was a cross-sectional study of 400 adults aged 20-70 years residing in the central area of ​​Porto Alegre, the capital of Rio Grande do Sul state. Race and racial discrimination were assessed by self-reported race/skin color using the Experiences of Discrimination scale (EOD), respectively. The food environment was assessed using the Nutrition Environment Measures Survey in Stores (NEMS-S) tool. Food insecurity was assessed using the short version of the Brazilian Food Insecurity Scale (EBIA for short, in Portuguese). Poisson regression with robust variance was employed for the multivariate analysis. Results The prevalence of food insecurity was higher in areas with a poorer food environment (areas 1 and 3; 56.6% and 58.8%, respectively). Racial discrimination was associated with food insecurity, where every 1-point increase in the racial discrimination score increased the likelihood of food insecurity by 7% (prevalence ratio [PR] 1.07; 95% CI, 1.03-1.20). When stratifying the analyses by food environment, racial discrimination was associated with food insecurity only in areas with a poorer food environment (PR 1.06; 95% CI, 1.01-1.10). Conclusions Experiences of racial discrimination were associated with a higher prevalence of food insecurity in the study population. The community food environment was an effect modifier of this relationship, highlighting the relevance of interventions in the food environment focused on areas with a greater presence of Black people as a way of combating racism and food insecurity.